The appointment of members to the shariah advisory council of Central Bank of Malaysia: legal issues - Hussain, Mohammad Azam; Hassan, Rusni; Azhar, Alias; Hasan, Aznan (2015)
In Malaysia, the appointment of members to the Shariah Advisory Council of Central Bank of Malaysia is prescribed by Central Bank of Malaysia Act 2009 (Act 701). The Act stipulates the provisions pertaining to the eligible persons to be appointed to the Shariah Advisory Council, procedures, terms and conditions of appointment and also remuneration and allowances for the members of the Shariah Advisory Council. In this regard, the question arises whether the prescribed provisions are sufficient to regulate the appointment of members to the Shariah Advisory Council and free from any shortcomings. By using legal research methodology, this article analyse the entire provisions dealing with the appointment matter. This study found that, several loopholes exist in the statutory requirement of the existing law which need to be addressed by respective authoritative body in order to avoid any legal conflict in the future.